HUBUNGAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN STRES AKADEMIK PADA MAHASISWA AKHIR YANG SEDANG MENYUSUN SKRIPSI - Fivie Puji Lestari; Raihanatu Binqalbi Ruzain; Rosyida (Jurnal Ners Indonesia, 2023)
Peer social support has positive impacts on students who are writing their theses and tend to experience stress due to the pressures involved in the thesis writing process. The objective of this research is to investigate the relationship between peer social support and stress levels among students who were working on their theses at the Islamic University of Riau. The sample for this study consisted of 258 respondents who were selected using a Non-Probability Sampling technique (purposive sampling). Data was collected through questionnaires measuring stress levels and social support with questionnaires' reliability measured using Cronbach's alpha coefficients of 0.738 and 0.748, respectively. The results of the non-parametric Spearman correlation test showed a correlation coefficient of r = -0.377 and a p-value of 0.000 (p < 0.005), indicating a significant negative relationship between peer social support and stress levels among students in the final stages of writing their theses. The findings suggest that higher levels of social support are associated with lower levels of stress among students working on their theses. It is recommended to further expand the research to provide comprehensive information about the stress levels among students in the final stages of writing their thesis